The running performance characteristics of U16 and U18 inter-county Ladies Gaelic Football players: An analysis across halves, playing positions, and age grades - Teresa Molohan; Stephen Behan; Sarahjane Belton; David Nolan (PLoS ONE, 2026)
This study examined the running performance demands of U16 and U18 inter-county Ladies Gaelic Football match play across halves, playing positions, and age grades using 10 Hz portable GPS technology (Catapult One, Melbourne, Australia). A total of 113 inter-county players (U16: height 166 ± 5.5 cm, body mass 59.5 ± 6.8 kg; U18: height 168 ± 5.1 cm, body mass 63.0 ± 8.2 kg) participated in the study. Data from competitive championship matches were collected over two seasons from nine U16 and twelve U18 games, resulting in 76 (U16) and 107 (U18) player profiles, respectively. A mixed repeated measures multivariate analysis of variance (MANOVA) evaluated the effects of age grade, positional line (full-back, half-back, midfield, half-forward, full-forward), and half of play (1st vs. 2nd) on variables including: Total Distance (TD), High-Speed Running (HSR), Max Speed, Relative Distance (m·min -1 ), Distance in Speed Zones 4 and 5, Accelerations (≥ 3 m·s ⁻ 2 ), and Decelerations (≤ −3 m·s ⁻ 2 ). Multivariate analysis for within- and between-subjects factors showed significant main effects for halves of play ( p < 0.001, η p 2 = 0.431), team ( p < 0.001, η p 2 = 0.300), and playing position ( p < 0.001, η p 2 = 0.183) on the combined dependent variables. Results demonstrated a consistent decline in running performance across halves, regardless of position or age. The ‘middle eight’ positions demonstrated the highest match-play demands and a distinct running profile compared to ‘inside’ lines, while U18 players showed significantly higher total and high-speed running distances than U16 players. This research is the first to examine the running performance profiles of U16 and U18 inter-county LGF players and may aid coaching by providing reference data for talent identification, individual player monitoring, and guiding developmental progression within the player pathway.